Mitral and tricuspid valve repair in an operated case of complete atrioventricular septal defect: A surgical challenge case report! - Dhanesh Kumar; Amit Chandra; Naresh Trehan; Shital Prakash; Yatin Mehta; Manisha Mishra; Surinder Bazaz; Sanjeev Chandna (SAGE Open Medical Case Reports)
Atrioventricular canal defects constitute about 3%–5% of total congenital heart defects, with a prevalence of 0.3–0.4/1000 live births. Mitral valve defects are associated with atrioventricular canal (septal) defects in most cases. Our case is of a 37-year-old male who underwent double patch closure of atrial and ventricular septal defects at the age of 24 years, now presenting with NYHA-III symptoms of severe mitral regurgitation and severe tricuspid regurgitation. The mitral valve was of atrio-ventricular canal type. We repaired both mitral and tricuspid valves using soft rings. Because of a deformed annulus, a soft ring was preferred.